Protein Chips Compatible with MALDI Mass Spectrometry Prepared by Ambient Ion Landing - Pompach, Petr; Benada, Oldřich; Rosůlek, Michal; Darebná, Petra; Hausner, Jiří; Růžička, Viktor; Volný, Michael; Novák, Petr (Analytical chemistry, 2016)
We present a technology that allows the preparation of matrix-assisted laser desorption/ionization (MALDI)-compatible protein chips by ambient ion landing of proteins and successive utilization of the resulting protein chips for the development of bioanalytical assays. These assays are based on the interaction between the immobilized protein and the sampled analyte directly on the protein chip and subsequent in situ analysis by MALDI mass spectrometry. The electrosprayed proteins are immobilized on dry metal and metal oxide surfaces, which are nonreactive under normal conditions. The ion landing of electrosprayed protein molecules is performed under atmospheric pressure by an automated ion landing apparatus that can manufacture protein chips with a predefined array of sample positions or any other geometry of choice. The protein chips prepared by this technique are fully compatible with MALDI ionization because the metal-based substrates are conductive and durable enough to be used directly as MALDI plates. Compared to other materials, the nonreactive surfaces show minimal nonspecific interactions with chemical species in the investigated sample and are thus an ideal substrate for selective protein chips. Three types of protein chips were used in this report to demonstrate the bioanalytical applications of ambient ion landing. The protein chips with immobilized proteolytic enzymes showed the usefulness for fast in situ peptide MALDI sequencing; the lectin-based protein chips showed the ability to enrich glycopeptides from complex mixtures with subsequent MALDI analysis, and the protein chips with immobilized antibodies were used for a novel immunoMALDI workflow that allowed the enrichment of antigens from the serum followed by highly specific MALDI detection.
Keywords: čipová analýza proteinů; ionty; povrchové vlastnosti; Protein Array Analysis; Ions; spektrometrie hmotnostní - ionizace laserem za účasti matrice; proteiny; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Surface Properties; Proteins